Kandungan C-Organik Substrat Ekosistem Mangrove di Danau Air Asin Gili Meno Kabupaten Lombok Utara - Firman Ali Rahman; Alfian Pujian Hadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Gili Meno Lake is one of the salt water lakes located in North Lombok Regency, West Nusa Tenggara Province. Gili Meno saltwater lake has an area of 6.6 hectares with a diversity of biota (flora and fauna) and unique physical and chemical characteristics of the lake waters. The purpose of this study was to determine the total c-organic content of the mangrove ecosystem and the c-organic content contained in the bottom substrate of mangrove stands. This type of research is descriptive quantitative with purposive random sampling method, which starts with sampling the substrate found under mangrove stands and testing in the laboratory using the Walkley & Black method to obtain carbon content. Based on the results of the study found 5 (five) types of mangroves, namely: 1) Avecennia marina; 2) Bruguera cylindrica; 3) Rhizophora apiculata; 4) Lumnitzera racemosa; and 5) Excoecaria agallocha, with the most dominant species being Avecennia marina. The largest % content of substrate carbon was found in the mangrove species Rhizophora apiculata with a total content of 19.995 %C or equivalent to 307.96 tons C/ha. Meanwhile, the potential for the estimated total carbon content of the substrate in the saltwater lake mangrove ecosystem of Gili Meno is 154.2 ± 99.78 tons C/ha or equivalent to 1020.50 tons C in a total of 6.6 hectares of mangrove ecosystem area of the saltwater lake Gili Meno.